Telaah Kritis Nilai-nilai Kebudayaan Islam “Studi Kasus Tradisi Ramadhan & Idul Fitri di Desa Pageraji Kabupaten Banyumas” - Faiq Fauziya Putri, Fatoni Achmad dan (Sekolah Tinggi Islam Blambangan Banyuwangi, 2019)
Abstract: In doing good deeds, each region in the world has its own characteristics. The custom then experienced a mix with Islamic traditions which ultimately created a harmony without leaving the applicable Shari'a. Acculturation of local culture with Islamic culture also occurred in Pageraji Village, Cilongok District, Banyumas Regency, Central Java. The Pageraji village community has a number of customs related to Islam that are still enduring today. The tradition is that the tarawih prayer time is slightly different from other regions, which is between 22:00 - 23:00, and the tradition of eating together and grave pilgrimage after the Eid prayer.